2022
DOI: 10.3390/ijerph192214854
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Resilience and Psychological Distress during the COVID-19 Pandemic: A Systematic Review and Meta-Analysis

Abstract: This study examined the association between resilience and psychological distress in healthcare workers, the general population, and patients during the COVID-19 pandemic. We searched the PubMed, Web of Science, PsycInfo, Science Direct, and Nursing and Allied Health databases. Included articles examined healthcare workers (e.g., physicians and nurses), the general population, and patients during the COVID-19 pandemic. Studies of exposure to other infectious diseases related to epidemics or pandemics (e.g., SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 97 publications
1
6
0
Order By: Relevance
“…The obtained results confirmed that resilience contributed to the explanation of each of the dimensions of mental health; more precisely, the greater the resilience of healthcare workers, the lesser the depression, anxiety, and stress they experienced, which is in line with the results of numerous studies conducted around the world during the pandemic [ 32 ]. Resilience is a dynamic process of adaptability to difficult life circumstances that includes several features of personal resources and was considered a protective factor against mental health problems in healthcare workers even before the outbreak of the COVID-19 pandemic [ 6 ].…”
Section: Discussionsupporting
confidence: 83%
“…The obtained results confirmed that resilience contributed to the explanation of each of the dimensions of mental health; more precisely, the greater the resilience of healthcare workers, the lesser the depression, anxiety, and stress they experienced, which is in line with the results of numerous studies conducted around the world during the pandemic [ 32 ]. Resilience is a dynamic process of adaptability to difficult life circumstances that includes several features of personal resources and was considered a protective factor against mental health problems in healthcare workers even before the outbreak of the COVID-19 pandemic [ 6 ].…”
Section: Discussionsupporting
confidence: 83%
“…Literature confirms the positive effect of resilience on individuals’ life. In particular, a meta-analysis found a significant negative correlation between resilience and psychological distress in COVID-19 patients (Jeamjitvibool et al, 2022). Similarly, a meta-analysis including patients with a somatic illness or health problem found a negative relationship between resilience and anxiety and depression (Färber & Rosendahl, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The positive impact of resilience and social support during the pandemic has already proven. In particular, a meta-analysis found a significant negative relationship between resilience and psychological distress among COVID-19 patients (Jeamjitvibool et al, 2022). Moreover, a review including workers found that resilience was associated with lower levels of anxiety, depression and burnout (Finstad et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Several meta-analyses confirm the positive effect of resilience on individuals’ life. For example, higher levels of resilience decrease psychological distress in COVID-19 patients (Jeamjitvibool et al, 2022). Moreover, during the pandemic resilience acted as a protective factor maintaining good quality of life among people (Aldhahi et al, 2021; Javellana et al, 2022; Koivunen et al, 2022) Also, there is a negative relationship between resilience and anxiety and depression among patients with a somatic illness or health problem (Färber & Rosendahl, 2018).…”
Section: Discussionmentioning
confidence: 99%